2017
DOI: 10.1177/1010428317711314
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CCAT2 promotes cell proliferation and invasion through regulating Wnt/β-catenin signaling pathway in clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is a common urologic malignancy. Long non-coding RNA colon cancer-associated transcript 2 (CCAT2) has been suggested as serving pivotal roles in tumorigenesis. However, the clinical significance and biological role of CCAT2 in ccRCC remains elusive. The purpose of this study is to identify the function of CCAT2 in ccRCC and its possible molecular mechanism. Expression of CCAT2 was analyzed in 61 ccRCC tissues and two ccRCC cell lines (786-O and ACHN) by quantitative reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…47 In our study, host gene USP34 of SNORA70B was mainly involved in regulating WNT signalling pathway. Moreover, they were involved in renal development and initiation of several renal diseases including kidney malignancy.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…47 In our study, host gene USP34 of SNORA70B was mainly involved in regulating WNT signalling pathway. Moreover, they were involved in renal development and initiation of several renal diseases including kidney malignancy.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, they were involved in renal development and initiation of several renal diseases including kidney malignancy. 47 In our study, host gene USP34 of SNORA70B was mainly involved in regulating WNT signalling pathway.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, large amount of researches have demonstrated that many lncRNAs such as HOTAIR, and metastasis associated lung adenocarcinoma transcript 1 (MALAT1) are highly expressed in colorectal cancer, breast cancer, hepatocellular carcinoma and some other cancer tissues and are closely related to a variety of cancer metastasis, thus can be used as targets for cancer early diagnosis, treatment and prognosis prediction [17,18]. CCAT2, as a novel oncogene, is located in the hotspot of tumour-related rs6983267 SNP, which promotes the occurrence and development of kinds of cancers by affecting Wnt and TGF-b signalling pathways [9,19]. Such as Xie et al reported that CCAT2 was overexpressed in endometrial cancer and knockdown of CCAT2 inhibited endometrial cancer cells growth and metastasis via sponging miR-216b [20].…”
Section: Discussionmentioning
confidence: 99%
“…Different long non-coding RNAs (lncRNAs) can also modulate the Wnt pathway at transcriptional to post-translational levels [64]. In a ccRCC cell line, the colon cancer-associated transcript 2 (CCAT2) promoted the ccRCC tumorigenesis [65] whereas LINC01510 negatively governed the canonical pathway and suppressed cell proliferation, invasion, EMT and promoted the apoptosis of ccRCC [66].…”
Section: Role Of Wnt In Ccrccmentioning
confidence: 99%